Association Between Gross-Motor and Executive Function Depends on Age and Motor Task Complexity. - Spedden, Meaghan E.; Malling, Anne Sofie B.; Andersen, Ken K.; Jensen, Bente R. (Developmental Neuropsychology, 2017)
The objective was to examine associations between motor and executive function across the adult lifespan and to investigate the role of motor complexity in these associations. Young, middle-aged and older adults (n = 82; 19-83y) performed two gross-motor tasks with different levels of complexity and a Stroop-like computer task. Performance was decreased in older adults. The association between motor and cognitive performance was significant for older adults in the complex motor task (p = 0.03, rs = -0.41), whereas no significant associations were found for young or middle-aged groups, suggesting that the link between gross-motor and executive function emerges with age and depends on motor complexity.